Climatic mass balance of the ice cap Vestfonna, Svalbard: A spatially distributed assessment using ERA-Interim and MODIS data ... - Möller, Marco; Finkelnburg, Roman; Braun, Matthias; Hock, Regine; Jonsell, Ulf; Pohjola, Veijo A; Scherer, Dieter; Schneider, Christoph (Humboldt-Universität zu Berlin, 2011)
The ice cap Vestfonna in the northern Svalbard archipelago is one of the largest ice bodies of the European Arctic (∼2400 km2), but little is known about its mass balance. We model the climatic mass balance of the ice cap for the period September 2000 to August 2009 on a daily basis. Ablation is calculated by a spatially distributed temperature-radiation-index melt model. Air temperature forcing is provided by ERA-Interim data that is downscaled using data from an automatic weather station operated on the ice cap. Spatially distributed net shortwave radiation fluxes are obtained from standard trigonometric techniques combined with Moderate Resolution Imaging Spectroradiometer-based cloud cover and surface albedo information. Accumulation is derived from ERA-Interim precipitation data that are bias corrected and spatially distributed as a function of elevation. Refreezing is incorporated using the Pmax approach. Results indicate that mass balance years are characterized by short ablation seasons (June to ...